The Ocean – Continent Transition Zones Along the Appalachian – Caledonian Margin of Laurentia: Examples of Large-Scale Hyperextension During the Opening of the Iapetus Ocean - Chew, David; van Staal, Cees (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
A combination of deep seismic imaging and drilling has demonstrated that the ocean-continent transition (OCT) of present-day, magma-poor, rifted continental margins is a zone of hyperextension characterized by extreme thinning of the continental crust that exhumed the lowermost crust and/or serpentinized continental mantle onto the seafloor. The OCT on present-day margins is difficult to sample, and so much of our knowledge on the detailed nature of OCT sequences comes from obducted, magma-poor OCT ophiolites such as those preserved in the upper portions of the Alpine fold-and-thrust belt. Allochthonous, lens-shaped bodies of ultramafic rock are common in many other ancient orogenic belts, such as the Caledonian – Appalachian orogen, yet their origin and tectonic significance remains uncertain. We summarize the occurrences of potential ancient OCTs within this orogen, commencing with Laurentian margin sequences where an OCT has previously been inferred (the Dalradian Supergroup of Scotland and Ireland and the Birchy Complex of Newfoundland). We then speculate on the origin of isolated occurrences of Alpine-type peridotite within Laurentian margin sequences in Quebec – Vermont and Virginia – North Carolina, focusing on rift-related units of Late Neoproterozoic age (so as to eliminate a Taconic ophiolite origin). A combination of poor exposure and pervasive Taconic deformation means that origin and emplacement of many ultramafic bodies in the Appalachians will remain uncertain. Nevertheless, the common occurrence of OCT-like rocks along the whole length of the Appalachian – Caledonian margin of Laurentia suggests that the opening of the Iapetus Ocean may have been accompanied by hyperextension and the formation of magma-poor margins along many segments.